The Pengaruh self-construal terhadap social media social comparison pada mahasiswa di Indonesia - Tedjawidjaja, Detricia; Christanti, Dessi (Jurnal Psikologi Ulayat, 2024)
Self-comparison on social media tends to harm mental health. Students, as some of the most active social media users, are particularly susceptible to self-comparison on these platforms. Self-construal is a cultural factor that influences the level of social media self-comparison. This research examines whether independent and interdependent construal affects self-comparison in college students. Participants in this research were 485 students aged 18–25 years who used social media. The data obtained was analyzed using regression analysis. The results of this study showed that only interdependent construal significantly predicts social media self-comparison among students. At the same time, there is no correlation between independent construal and social media self-comparison. However, interdependent construal only contributes 2% to social media self-comparison. This research can provide an overview of how cultural factors, especially certain self-construal types, can lead to the emergence of social media self-comparison.